Analisis Perubahan Interaksi Sosial dalam Proses Beribadah Umat Beragama Islam pada Masa Pandemi - Nopi Krisnawati; Widia Triyana; Fanny Rahmasari; Anis Hidayatul Ummah; Hisny Fajrussalam (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
Social interaction is something that will become a component of humans as social beings. Knowledge about social interaction is not centered on each individual alone but can be with groups in the form of social contact and communicating with a response. The establishment of social interaction can take place anywhere and anytime. With the Covid-19 virus, there has been a complete change in all human activities, including changes in social interaction. The changes that occur do not only have an impact on the social process but also have an impact on the worship process of every religious community. This study raises the issue of changes in social interaction in the process of worshiping religious people who are focused on Islam. The respondents in this study were addressed to the general public, students, and teachers/lecturers. The data collection technique used is through an e-questionnaire with google forms. From the research process conducted, it is stated that with this pandemic, the process of social interaction in carrying out the worship process for Muslims has undergone significant changes and is expected to provide information about changes in social interaction and can be developed in a better direction.